PENDEKATAN TRIANGULAR FUZZY NUMBER DALAM METODE ANALYTIC HIERARCHY PROCESS - Anshori, Yusuf (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
The study aims to design decision support system using triangular fuzzy number approach in Analytic Hierarchy Process method. The Analytic Hierarchy Process (AHP) is one of the decision support system method which controls experiences and intuition but critical at coupled comparative scales because it uses crisp. A triangular fuzzy number is used to approach AHP scale so as to obtain more fexible value of coupled comparison. The triangular fuzzy number-AHP method uses analysis synthetic extent in the priority processing implemented on ranking cases of potential acceptors of scholarship of PPA and BBM in Technic Faculty Tadulako University of Palu. The result is the average of mismatch between the result by triangular fuzzy number-AHP method and the result of manual work which are 23.93% of the PPA scholarship and 27,35% of the BBM scholarship. Â  Keyword :Triangular Fuzzy Number, Analytic Hierarchy Process, scholarship